Pathophysiology of acute renal failure - Calice-Silva, Viviane (Henry Stewart Talks, 2024)
Acute renal failure, Acute Kidney Injury (AKI), Epidemiology and pathophysiology of AKI, KDIGO, Chronic Kidney Disease (CKD), Acute Kidney Disease (AKD), Risk factors of acute kidney injury, Burden of acute kidney injury, Etiology of acute kidney injury